2006
DOI: 10.1111/j.1440-1819.2006.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of error negativity and positivity in schizophrenia patients

Abstract: The purpose of the present paper was to determine error-monitoring ability and its relationship with executive function in patients with schizophrenia. In order to evaluate error-monitoring ability, the error negativity (Ne) and error positivity (Pe) were measured using the Stroop task. The correct-related negativity (CRN) and positivity (Pc) were also measured. In addition, neuropsychological tests were administered in order to evaluate executive function. The patients with schizophrenia had significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 25 publications
12
60
3
Order By: Relevance
“…Instead, this literature suggests that ACC abnormalities and error processing deficits are trait markers of genetic vulnerability to schizophrenia that predate the onset of illness. Impairments in evaluating and learning from errors in schizophrenia may substantially contribute to the rigid, perseverative, and maladaptive patterns of thought and behavior that characterize schizophrenia and compromise social and occupational function (Kim et al, 2006). In support of this possibility, a recent study reported that a blunted ERN was associated with more severe negative symptoms and poorer real world function as indicated by unemployment and re-hospitalization (Foti et al, 2012).…”
Section: Schizophreniamentioning
confidence: 99%
“…Instead, this literature suggests that ACC abnormalities and error processing deficits are trait markers of genetic vulnerability to schizophrenia that predate the onset of illness. Impairments in evaluating and learning from errors in schizophrenia may substantially contribute to the rigid, perseverative, and maladaptive patterns of thought and behavior that characterize schizophrenia and compromise social and occupational function (Kim et al, 2006). In support of this possibility, a recent study reported that a blunted ERN was associated with more severe negative symptoms and poorer real world function as indicated by unemployment and re-hospitalization (Foti et al, 2012).…”
Section: Schizophreniamentioning
confidence: 99%
“…Reduction of ERN amplitude is a robust abnormality reported in multiple studies of cases with established schizophrenia (Kopp and Rist, 1999;Alain et al, 2002;Bates et al, 2002;Mathalon et al, 2002;Kim et al, 2006;Morris et al, 2006Morris et al, , 2008Mathalon et al, 2009;Horan et al, 2011;Perez et al, 2011). While there is some evidence that the abnormality diminishes during treatment (Bates et al, 2004), recent studies report abnormal ERN in individuals exhibiting behaviour indicating risk of schizophrenia (Laurens et al, 2010) and in clinical high-risk individuals (Perez et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The amplitude and latency of the components were retrieved from the following electrode sites: Fz, FCz and Cz (Kim et al, 2006). Fig.…”
Section: Erps Datamentioning
confidence: 99%